(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The present study was carried out from 1st August 2011 to 31 January 2012 to identify mosquilo species inhabiting in and around the Dhaka Cantonment. In all 3632 samples sue were collected from 88 different spots. Important three genera such as Anopheles, Odex ad Aides were found and distribution was as Culex 5581 (99.09%), Aedes 30 (0.53%) and Anopheles 21 (0.37%). Among the Culex species C. quinquefasciatus Dominated and having 69.37% of Culex family. Other identified species were C. ftacocephaia (14.89%), C. tritaeniorhynchus (09.07%) and C. vishnul (06.67%). The distribution of the sampled mosquitoes revealed that female dominated and male female ratio was 34:66. There was predominance of C. quinquefasciatus in all coUeakm points. Anopheles was identified 21 (12 female) in number of which An. phUiptmmd was 17 and An. aconitus only 04 and they were collected from four spots of Zxu colony and COD areas. Ae. aegypti was identified 30 (22 female) in number of which Ae aegypti were 23 and the rest 07 were Ae albopictus and they were collected from seven spots of COD, Senapolli, Moinul Road and DOHS Mohakhali but its density a very insignificant and below the critical level of disease transmission. Asiat. Soc. Bangladesh, Sci. 40(2): 243-248, December 2014